The side effects of safe asset creation - Sushant Acharya; Keshav Dogra (Bank of Canada, 2021)
We present an incomplete markets model to understand the costs and benefits of increasing government debt when an increased demand for safety pushes the natural rate of interest below zero. A higher demand for safe assets causes the ZLB to bind, increasing unemployment. Higher government debt satiates the demand for safe assets, raising the natural rate and restoring full employment. However, this entails permanently lower investment, which reduces welfare, since our economy is dynamically efficient even when the natural rate is negative. Despite this, increasing debt until the ZLB no longer binds raises welfare when alternative instruments are unavailable. Higher in inflation targets instead allow for negative real interest rates and achieve full employment without reducing investment.
Keywords: E3; E4; E5; G1; H6; 330; Monetary policy implementation; Fiscal policy